First case of piebaldism in Eumops auripendulus in Costa Rica - Mora, José M.; Sánchez, Ronald (Therya Notes, 2022)
Pigmentation anomalies are caused either by a deficiency in, or an excess of melanin, resulting in chromatic disorders of the skin and fur or feathers. The anomaly consisting of white spotting has been reported in bats as leucism or piebaldism. We present the first record of piebaldism in Eumops auripendulus in Costa Rica. While monitoring bats in urban areas we measured the forearm of all specimens and noted (among other traits) coat color and length of ears. We checked individuals for the presence of glands and assessed the degree of ossification of the epiphyseal plates in the phalangeal joints. On September 13, 2021, we found a dead male E. auripendulus in San Ramón, Costa Rica. The forearm measured 57.5 mm, which is within the range of 57 – 63 mm reported for the species. The bat was a juvenile individual with a white spot in the middle of the abdominal region. Similar instances of aberrant coloration have been defined as piebaldism. The record of a piebald E. auripendulus is the second one for a molossid bat done in Costa Rica in a total of 6 cases of chromatic disorders. These aberrant colorations could be related to potentially detrimental circumstances; for example, the presence of white spots may be associated with deafness, which in the case of bats would prevent individuals from using echolocation. Knowledge of cases of color anomalies in bats will help to understand the ecological and physiological implications of this condition.